Argumentative Role Ethics in Islamic Dialogue Theory - Oruç, Rahmi (Informal Logic, 2026)
Islamic dialogue theory, developed through the Munāẓara tradition, introduces a distinct model of argumentation and a unique type of dialogue not yet captured by existing typologies. While pragma-dialectics upholds a single, idealized normative framework, and dialogue theory distributes norms across multiple types, Stevens (2026) argues that both neglect the ethical responsibilities built into argumentative practice. Building on her account, I show that in munāẓara, argumentative roles are procedurally indeterminate and inherently negotiable. Decisions about sequencing, burden of proof, what counts as a move, and how one flavors a role involve a continuous negotiation of the rights and obligations of each party.